Transgenic Mice Expressing Human α-Synuclein 1-103 Fragment as a Novel Model of Parkinson’s Disease - Tian, Ye; He, Mingyang; Pan, Lina; Yuan, Xin; Xiong, Min; Meng, Lanxia; Yao, Zhaohui; Yu, Zhui; Ye, Keqiang; Zhang, Zhentao (Frontiers in Aging Neuroscience, 2021)
Parkinson’s disease (PD) is one of the most common neurodegenerative disorders. However, its cellular and molecular mechanisms still wrap in the mist. This is partially caused by the absence of appropriate animal models mimicking sporadic PD that constitutes the majority of cases. Previously we reported that a cysteine protease, asparagine endopeptidase (AEP), is activated in an age-dependent manner, and cleaves α-synuclein in the brain of sporadic PD patients. The AEP-derived α-synuclein 1-103 fragment is required for the pathogenesis of PD. Thus, we designed and characterized a novel transgenic mouse line expressing α-synuclein 1-103 (designated N103 mice). This model shows an abundant accumulation of pathological α-synuclein in the central nervous system, loss of dopaminergic neurons in the substantia nigra, and progressive striatal synaptic degeneration. The N103 mice also manifest age-dependent PD-like behavioral impairments. Notably, the mice show weight loss and constipation, which are the common non-motor symptoms in PD. The RNA-sequencing analysis found that the transcriptomics pattern was extensively altered in N103 mice. In conclusion, the N103 mouse line, as a brand-new tool, might provide new insights into PD research.